Causative mutations and premature cardiovascular disease in patients with heterozygous familial hypercholesterolaemia. (29th August 2020) - Rubba, Paolo; Gentile, Marco; Marotta, Gennaro; Iannuzzi, Arcangelo; Sodano, Marta; De Simone, Biagio; Jossa, Fabrizio; Iannuzzo, Gabriella; Giacobbe, Carola; Di Taranto, Maria D; Fortunato, Giuliana
Abstract: Background: Familial hypercholesterolemia is a common autosomal dominant disease, caused by mutations leading to elevated low-density lipoprotein (LDL) cholesterol and, if untreated, to premature cardiovascular disease. Methods: Patients (young adults with a family history of hypercholesterolaemia or premature cardiovascular disease) with LDL cholesterol concentration ≥4.9 mmol/l, after excluding Familial Combined Hyperlipidaemia, were evaluated for causative mutations, Dutch Lipid Clinic Network score calculation and non-invasive ultrasound examination of carotid arteries. Results: Of the 263 patients, 210 were heterozygotes for LDL receptor ( LDLR ) mutations, four had APOB gene mutations, one PCSK9 gene mutation, while 48 had no evidence of mutations. Among 194 unrelated index cases 149 had mutations (77%). Among patients with LDLR mutations ( n = 145), there were five compound heterozygotes, 75 patients with null mutations and 65 with missense mutations. As many as 178 patients underwent a follow-up and treatment (statin ± ezetimibe), achieving a mean reduction of 49% in LDL cholesterol, with 21% of patients reaching the LDL goal of 2.6 mmol/l. In a multivariate analysis, carotid plaques, at ultrasound examination, were associated with the presence of genetic mutation ( p = 0.001), LDL cholesterol ( p < 0.001), Dutch Lipid Clinic Network score ( p < 0.001), independently of age, gender, smoking habits and systolic blood pressure. The presence of carotid plaque ( p = 0.017), LDL cholesterol ( p < 0.003), Dutch Lipid Clinic Network score ( p < 0.001) were independently associated with premature cardiovascular disease. Conclusions: We identified patients with causative mutations in 82% of the cases under study. In addition to LDL cholesterol and Dutch Lipid Clinic Network score, carotid plaques in ultrasound evaluation provide direct evidence of premature vascular disease and are associated with high risk for cardiovascular events.